Collecting Taxes - McLeod, Rob (Victoria University of Wellington Law Review, 2002)
In this issue celebrating Sir Ivor Richardson’s career, the author praises Sir Ivor’s contributions to the field of tax law. The author focuses on three aspects of taxation: interpreting tax legislation, resolving tax disputes, and the application of economic analysis to law. With regards to interpretation, the author notes a shift to purposive interpretation by the courts as a positive thing for targeting tax avoidance, although the author also argues that tax avoidance legislation still has room for improvement. With regards to the resolution of tax disputes, the author agrees with Sir Ivor’s Review Committee in that a revised tax disputes resolution process and a fast-track procedure should both be introduced. With regards to the application of economic analysis to law, the author argues that more emphasis should be given to economic analysis and demonstrates the value of a theoretical framework for income tax reform. It is concluded that Sir Ivor’s qualities have been enduring and ensured his contribution to the New Zealand tax system.